1984
DOI: 10.1002/hep.1840040703
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Primary Hepatocellular Carcinoma

Abstract: Prognosis of 600 consecutive patients with hepatocellular carcinoma was analyzed in relation to treatment. They were divided into three stages based on four parameters of advanced disease: ascites, tumor greater than 50% of the two-dimensional size of the liver, serum albumin below 3 gm per dl, and serum bilirubin above 3 mg per dl. Stage I had none of these signs; Stage I1 one or two signs, and Stage 111 three or all signs. Of 600 patients, 98 had resection, 333 had nonsurgical treatment (1 58 treated by intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
2
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(106 citation statements)
references
References 10 publications
5
97
2
2
Order By: Relevance
“…Previous study showed that the reduced serum level of AFP after intervention, the number of TACE procedures, small tumor size anda homogenous tumor uptake are related to the prognosis of patients treated with TACE (Okuda et al, 1984;Mondazzi et al, 1994;Farinati et al, 1996;Savastano et al, 1999;Lee et al, 2002;Lopez et al, 2002), which showed the difference on the prognosis of HCC could be due to ethnicity, characteristics of patients or chance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that the reduced serum level of AFP after intervention, the number of TACE procedures, small tumor size anda homogenous tumor uptake are related to the prognosis of patients treated with TACE (Okuda et al, 1984;Mondazzi et al, 1994;Farinati et al, 1996;Savastano et al, 1999;Lee et al, 2002;Lopez et al, 2002), which showed the difference on the prognosis of HCC could be due to ethnicity, characteristics of patients or chance.…”
Section: Discussionmentioning
confidence: 99%
“…The local recurrence rate for HCC was 0% for a mean follow-up of 18.4 months (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Table 5.…”
Section: Tumor Recurrencementioning
confidence: 99%
“…Other risk factors related included chronic hepatitis C virus (HCV) infection, heavy alcohol intake, dietary aflatoxin exposure, the male gender and chronic liver disease of any type. [2][3][4] While the causative links with the etiologic factors are now well recognized, the molecular events involved in the progression of HCC remain largely unclear.…”
mentioning
confidence: 99%